The Construction of Indigenous Identity Through Creativity: An Exploration of Māori and Pacific Identity Constructed Through Dance, Visual Arts, and Creative Writing - Matelau-Doherty, Tui (Auckland University of Technology, 2020)
This thesis examines the construction of hybrid and fluid ethnic identity elements as produced by Māori and Pacific female artists. Ethnic identity studies within New Zealand reveal different types of ethnic identities, and although there is research being conducted into hybrid and fluid Māori and Pacific identity elements, no studies have been done examining the construction of these identities through mediated action. This thesis attempts to fill this gap. Using video ethnography and socio-linguistic interviews, data were collected and analysed utilising multimodal (inter)action analysis (MIA) as the theoretical and methodological framework. Vertical identity production and site of engagement are analytical tools within MIA that allow for the study of the intersection between discourses and mediated actions performed by social actors. These analytical tools were applied to interview and video transcripts selected from the data, following a systematic process of data cataloguing. Analysis of the data is presented in three chapters which show the ethnic and creative identity production of the participants as constructed through the central, intermediary and outer layers of discourse. The first analysis chapter demonstrates the way the participants create art by blending traditional and contemporary features and diverse knowledge, in turn constructing their immediate ethnic and creative identity elements. This analysis is compared to the way the participants verbalise these identity elements within their interviews. The second analysis chapter examines the way experiences of exclusion and inclusion from within their networks shape their continuous ethnic and creative identity elements. The third analysis chapter explores moments of exclusion and inclusion but within larger communities such as mainstream New Zealand, and their ethnic communities. It also illustrates the way in which the participants’ art creates inclusion and shapes the general ethnic and creative identity development of other social actors. Following this, wider discourses and practices are examined using the site of engagement as the analytical tool. This chapter demonstrates the way in which wider discourses such as colonial, superiority/inferiority and racism discourse intersect with practices such as superiority/inferiority, gratitude, and marginalisation and with the mediated actions performed by the participants. This analysis highlights the negative impact these discourses and practices can have on ethnic identity construction for Māori and Pacific social actors. To this end, numerous recommendations are made within the conclusion with the intention of changing these wider discourses and practices. This thesis contributes to knowledge in the area of Māori and Pacific identity studies by utilising multimodal (inter)action analysis to study identity production. It also contributes to the theoretical and methodological framework of multimodal (inter)action analysis.
Keywords: Identity; Ethnic identity; Māori identity; Pacific identity; Creative practice; Multimodal (inter)action analysis; Indigenous identity